DISCLOSURE OF GREEN ACCOUNTING ON FINANCIAL PERFORMANCE - rizal, noviansyah; Mimin Yatminiwati (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
This study aims to determine the effect of environmental accounting disclosures on stock performance on companies listed on the Indonesia Stock Exchange. Companies that already run their businesses, then there is a possibility that these companies have great potential to have positive and negative impacts on market needs. The sample of this research is the manufacturing sector from 2011-2015. The data analysis technique used is a simple linear regression analysis by analyzing the independent variables of environmental accounting disclosure measured using proper in influencing the dependent variable of stock performance measured using stock returns. The results of this study show that environmental accounting disclosures have a positive effect on stock performance.